Opportunity cost of high-cost medicines and health decisions in times of pandemic - Hasdeu, Santiago (2021)
Introduction: Making fair coverage decisions by allocating limited resources implies prioritization. Given the pandemic, this is even more difficult, given the economic recession and the need to cope with new demands for health technologies, in addition to the rest of the needs of the health system. Health Technology Assessment and the regulation of drug prices are two strategies recommended by WHO-PAHO to increase the efficiency and equity of health systems. We analize the budget impact and opportunity cost of spinraza, a high-cost drug that would be effective in increasing the survival of patients with a rare disease named Type I Spinal Muscular Atrophy. In Argentina, it is covered without price regulation, paying three times more expensive than in Brazil, although a National Health Technology Assessment did not recommend this. Methods: The opportunity cost of spinraza for Spinal Muscular Atrophy is expressed as the possibility of purchasing mechanical respiratory assistance equipment, which has become a universal priority in the pandemic context. At the current sale price, and for 100 estimated patients with Type I Spinal Muscular Atrophy under treatment, Argentina invests in spinraza funds equivalent to those needed to buy 2 417 respirators, with which it could have increased its installed equipment capacity by 35% at the beginning of the pandemic. Acceptability curves for coverage of these technologies and scenarios of potential lives saved in the face of different types of drug price reduction were analyzed. Discussion: Argentina, like other countries in the region, must redesign decision-making processes on high-cost drug coverage to ensure the efficiency, equity, and sustainability of the health system. The pandemic context can be an opportunity to base decisions on tools such as prioritization based on health technology assessment with binding recommendations, estimating the opportunity cost of interventions, and regulating the prices of high-cost drugs.